DESENVOLVIMENTO DE HEMATOMAS NA VEIA DE BOVINOS USANDO DIFERENTES COLETORES DE SANGUE - SOARES, Vitória; FONSECA, Fabianna Costa; SILVA, Evellyn Richelly Ferreira; OLIVEIRA, Dalton Mendes; OLIVEIRA, Marcus Vinicius Morais (ANAIS DO ENIC, 2018)
-